Biomedical Devices: Biomimicking Antibacterial Opto‐Electro Sensing Sutures Made of Regenerated Silk Proteins (Adv. Mater. 1/2021). Issue 1 (4th January 2021) - Liu, Mengwei; Zhang, Yujia; Liu, Keyin; Zhang, Gai; Mao, Ying; Chen, Liang; Peng, Yinbo; Tao, Tiger H.
Abstract : In article number 2004733, Liang Chen, Yinbo Peng, Tiger H. Tao, and co‐workers report a silk‐protein‐based biomimetic sensing suture, which integrates multiple, clinically favorable functions including strain sensing, controlled delivery of medical factor(s) with real‐time monitoring, wound temperature control, and antibacterial activity.